2013
DOI: 10.3892/mmr.2013.1759
|View full text |Cite
|
Sign up to set email alerts
|

More efficient induction of antitumor T cell immunity by exosomes from CD40L gene-modified lung tumor cells

Abstract: The incidence of lung cancer increases annually. However, the effects of the present methods for the treatment of lung cancer are extremely poor. It has been reported that exosomes from heat‑stressed 3LL Lewis lung tumor cells effectively elicit systemic antitumor immunity. CD40 signaling is critical in the activation of dendritic cells (DCs), which are important in the induction of antitumor immunity. In the present study, exosomes from CD40 ligand gene‑modified 3LL tumor cells (CD40L‑EXO) were identified to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 21 publications
0
49
0
Order By: Relevance
“…The isolated exosomes, verified by expression of exosome-specific markers TSG101, CD63, and HSP70 (Fig. 1b) [2527], were added into hESC-derived cultures in exosome-depleted DM on day 6. As expected, we found that after 10-day treatment with A549-derived exosomes, but not with hiPSC-ATIIC- or hATIIC-derived exosomes, the hESC-derived SPC-expressing cells were enriched to the degree similar to that observed in hESC-derived cultures treated with A549-CM, suggesting an exosome-mediated communication between ATIICs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The isolated exosomes, verified by expression of exosome-specific markers TSG101, CD63, and HSP70 (Fig. 1b) [2527], were added into hESC-derived cultures in exosome-depleted DM on day 6. As expected, we found that after 10-day treatment with A549-derived exosomes, but not with hiPSC-ATIIC- or hATIIC-derived exosomes, the hESC-derived SPC-expressing cells were enriched to the degree similar to that observed in hESC-derived cultures treated with A549-CM, suggesting an exosome-mediated communication between ATIICs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…81,84 Other successful examples based on this strategy included CD40L-modified lung cancer cells, CIITA-transfected CT26 cells and TNF-engineered J558 tumor cell. [85][86][87] Apart from genetic modification, external stimulus is added to drive tumor cell release of exosomes. We have extracted exosomes from a series of stress-induced tumor cells such as lymphoma cells, CEA-positive tumor cells, Lewis lung carcinoma and melanoma cells.…”
Section: Modified Tumor Cell-derived Exosomes (Texs)mentioning
confidence: 99%
“…Thus, the context in which they are presented is of high importance. Many different strategies, from using heat-shocked tumors cells [159,160] to having the cells express markers such as Hsp70 [161,162], CD40L [163], and Rab27a [164] have been proposed for improving immunogenicity. Instead of direct vaccination, tumor exosomes have been used as the antigenic material for pulsing dendritic cells to promote downstream immunity [165].…”
Section: Cell Membrane-based Nanostructuresmentioning
confidence: 99%